Upaya Peningkatan Kemampuan Berbicara Di Kelas I Sekolah Dasar Melalui Penggunaan Media Puppet - patimah, patimah (Journal of Innovation in Primary Education, 2023)
This research was motivated by the low speaking ability in Class I Elementary School. The aim of this research is to improve speaking skills in Class I elementary schools using Puppet media. This research is classroom action research with three cycles, each cycle carrying out two actions consisting of four activity stages, namely the planning stage, implementation stage, observation stage, and reflection stage. The subjects of this research were class my students in SD Negeri Kertajati I, Kertajati District, Majalengka Regency, totaling 26 students. Data collection techniques use observation, speaking ability tests, and documentation. The research instrument used was a learning activity observation sheet. The research results show that puppet media can improve speaking skills in grade I elementary school. Increasing speaking ability is influenced by student and teacher activities in the classroom learning process. Puppet media has a positive impact on students' enthusiasm for learning mathematics because it formulates learning techniques that are very fun so that students do not feel bored when studying the material.